Chapter 4 The Global War Against the Rat - Lynteris, Christos (The MIT Press, 2022)
It is almost impossible to find a plague-related news item today that is not accompanied by an image of a rat. The best-known carriers of zoonotic diseases, rats are so closely identified with plague that research articles about the role of other mammals in the spread or maintenance of the disease are met with enthusiasm in the media-and in some cases mistakenly hailed as exonerating rats from the spread of plague. This tautology between rat and plague is articulated in a context of framing an expanding range of nonhuman animals as hosts or vectors of infectious diseases such as influenza, Ebola, severe acute respiratory syndrome (SARS), and COVID-19